BIOMARKERS OF CARDIOVASCULAR COMPLICATIONS ASSOCIATED WITH COVID-19 DISEASE (World Science, 2023)
The coronavirus disease (COVID-19), which caused a global pandemic in the world, is now becoming an endemic, seasonal disease. Therefore, the search for new biomarkers to predict the course of the disease and its outcomes remains extremely important. It has been found that COVID-19 affects not only the respiratory system but also other organs and systems of the body. In particular, the target of the SARS-CoV-2 virus is the cardiovascular system. Because the severity of COVID-19 disease is highly variable, laboratory biomarkers can provide important prognostic information already at the emergency stage, especially in patients with atypical manifestations. It has been demonstrated that viral infections, and in particular COVID-19, can cause changes in the host's lipid profile. Changes in the processes of intracellular cholesterol biosynthesis and its transport in the bloodstream of patients with COVID-19 have been reported. Thus, in patients suffering from COVID-19, significantly reduced levels of total іукгь cholesterol (C), HDL, and LDL cholesterol, and an increased ratio of triglycerides/C have been recorded. Patients with COVID-19 are characterized by an increased content of residual (remnant) cholesterol, which is defined as cholesterol present in residual lipoproteins rich in triglycerides and, as shown by the results of genetic, observational, and clinical studies, is associated with the development of atherosclerosis and overall mortality. Several peptide cardiac biomarkers have become other predictors of cardiovascular prognosis in patients with COVID-19: highly sensitive cardiac troponin – successfully used in clinical practice as a marker of myocyte damage for diagnosis and prognostic assessment of acute coronary syndrome; N-terminal pro-B-type natriuretic peptide (NT-proBNP) is a biomarker of myocardial stretch; peptide ST2 – a marker of remodeling of myocardial extracellular matrix, which prevents fibrosis, cardiac hypertrophy and apoptosis; copeptin is a biomarker of neurohumoral activation. The review provides a concise analysis of currently known cardiac biomarkers in COVID-19 and their prognostic significance.